Development of Suspended Sediment Monitoring of the Tisza Using an Indirect Measurement Method - Tóth, Péter (Journal of Environmental Geography, 2023)
The Tisza River experienced successive flood peaks between 1998 and 2010. The reasons of the increased flood height are various, one of them is overbank floodplain accumulation. The aim of the present study is to apply and test an alternative sediment measurement method to evaluate the sediment transport of the Tisza River, Hungary. The new method could help practitioners to better understand the fluvial processes. A significant problem with the current sediment measurement practice is that it does not consider or just to a limited extent, the hydrological conditions of a river. The data measured at the turbidity measuring station installed in the Middle Tisza at Szolnok are evaluated to determine whether or not this measurement procedure can be applied for the highly various sediment transport conditions of the Tisza. In measurement campaigns and based on continuous data from the turbidity measuring probe, a close relationship between near-bank turbidity and suspended sediment concentration was established. The suspended sediment concentrations calculated from the near-bank turbidity were compared with the results of suspended sediment yield from a few cross-section measurements. The results are encouraging; despite the limited number of measurements, the relationship between the parameters is close. In order to make the method more precise, additional series of measurements are needed, which also cover the high water range.